The impact of permanent residents’ (PR) demand on HDB resale price in Singapore - Chua, Louis Wang Da (2015)
Immigration and the influx of foreigners to Singapore have increased rapidly over the years. This paper examines one outcome of foreign immigration to Singapore by focusing on prices in the property market. This paper analyzes the effects of the demand of Singapore Permanent Residents (PR) on the resale public housing market. Other factors that affect resale property prices such as income, interest rate and housing supplies are included as control variables. This study finds that when citizen’s demand is being added to the regression model, PRs’ demand becomes insignificant. Results of an alternative regression model, however, suggest that PRs exert no greater impact on HDB resale prices than that of citizens.